The ice age : a very short introduction - Woodward, Jamie C. (Very short introductions ;, 2014)
"In an era of warming climate, the study of the ice age past is now more important than ever. This book examines the wonders of the Quaternary ice age - to show how ice age landscapes and ecosystems were repeatedly and rapidly transformed as plants, animals, and humans reorganized their worlds." --Publisher.